Web Reasoning and Rule Systems Third International Conference, RR 2009, Chantilly, VA, USA, October 25-26, 2009, Proceedings - Polleres, Axel; Swift, Terrance (Information Systems and Applications, incl. Internet/Web, and HCI, 2009)
This book constitutes the refereed proceedings of the Third International Conference on Web Reasoning and Rule Systems, RR 2009, held in Chantilly, VA, USA, in October 2009. The 15 revised full papers presented together with 3 invited papers were carefully reviewed and selected from 41 submissions. The papers address all current topics in Web reasoning and rule systems such as proof/deduction procedures, scalability, uncertainty, knowledge amalgamation and querying, and rules for decision support and production systems.